Evidence for the efficacy of melatonin in the treatment of primary adult sleep disorders. (August 2017) - Auld, Fiona; Maschauer, Emily L.; Morrison, Ian; Skene, Debra J.; Riha, Renata L.
Summary: Melatonin is a physiological hormone involved in sleep timing and is currently used exogenously in the treatment of primary and secondary sleep disorders with empirical evidence of efficacy, but very little evidence from randomised, controlled studies. The aim of this meta-analysis was to assess the evidence base for the therapeutic effects of exogenous melatonin in treating primary sleep disorders. An electronic literature review search of MEDLINE (1950-present) Embase (1980- present), PsycINFO (1987- present), and Scopus (1990- present), along with a hand-searching of key journals was performed in July 2013 and then again in May 2015. This identified all studies that compared the effect of exogenous melatonin and placebo in patients with primary insomnia, delayed sleep phase syndrome, non 24-h sleep wake syndrome in people who are blind, and rapid eye movement-behaviour disorder. Meta-analyses were performed to determine the magnitude of effect in studies of melatonin in improving sleep. A total of 5030 studies were identified; of these citations, 12 were included for review based on the inclusion criteria of being: double or single-blind, randomised and controlled. Results from the meta-analyses showed the most convincing evidence for exogenous melatonin use was in reducing sleep onset latency in primary insomnia (p = 0.002), delayed sleep phase syndrome (p < 0.0001), and regulating the sleep-wake patterns in blind patients compared with placebo. These findings highlight the potential importance of melatonin in treating certain first degree sleep disorders. The development of large-scale, randomised, controlled trials is recommended to provide further evidence for therapeutic use of melatonin in a variety of sleep difficulties.